INNOVATIVE METHODS IN TEACHING CLINICAL PHARMACOLOGY AT A MEDICAL UNIVERSITY - G. H. Akhmedova,; M.I.Mukhitdinova,; F.U.Rakhmatova, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Relevance. The primary goal of professional education in a medical university is  the  training  of  qualified  physicians  who  are  capable  of  effective  work  in  their specialty  and  competitive  in  the  labor  market.  High-quality  education  is  strongly associated  with  the  goals  of  the  Bologna  Process:  academic  mobility,  diploma recognition, the introduction of credit systems, and innovative technologies in teaching and knowledge management (4). Currently, the main methodological innovations are directly related to the use of interactive teaching methods.